2017
DOI: 10.3390/membranes7030043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZnO Nanoparticle on the Gas Separation Performance of Polyurethane Mixed Matrix Membrane

Abstract: Polyurethane (PU)-ZnO mixed matrix membranes (MMM) were fabricated and characterized for gas separation. A thermogravimetric analysis (TGA), a scanning electron microscope (SEM) test and an atomic-force microscopy (AFM) revealed that the physical properties and thermal stability of the membranes were improved through filler loading. Hydrogen Bonding Index, obtained from the Fourier transform infrared spectroscopy (FTIR), demonstrate that the degree of phase separation in PU-ZnO 0.5 wt % MMM was more than the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…It was found that when ZnO nanomaterials were added into BMIMBF4, the selectivity of CO 2 /N 2 and CO 2 permeability were significantly enhanced. Our group has worked on PEBA composite membranes and also membranes with ZnO nanomaterials as filler in the last two years using both experimental test and simulation software.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when ZnO nanomaterials were added into BMIMBF4, the selectivity of CO 2 /N 2 and CO 2 permeability were significantly enhanced. Our group has worked on PEBA composite membranes and also membranes with ZnO nanomaterials as filler in the last two years using both experimental test and simulation software.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in selectivity was also reported for UiO66‐PU and MIL‐101‐PU MMMs, which can be ascribed to the low compatibility of the fillers with PU chains . However, in several other publications, it was reported that the addition of inorganic fillers (e.g., metal oxides such as ZnO, silica, alumina, and TiO 2 ) to the PU matrix led to higher selectivities but lower permeabilities . Interestingly, the incorporation of functionalized‐MOFs in PU membranes was found to increase the CO 2 /N 2 selectivity but not to change the CO 2 permeability appreciably .…”
Section: Introductionmentioning
confidence: 77%
“…58 However, in several other publications, it was reported that the addition of inorganic fillers (e.g., metal oxides such as ZnO, silica, alumina, and TiO 2 ) to the PU matrix led to higher selectivities but lower permeabilities. [59][60][61][62] Interestingly, the incorporation of functionalized-MOFs in PU membranes was found to increase the CO 2 /N 2 selectivity but not to change the CO 2 permeability appreciably. 46,63 Incorporation of 20 wt % SAPO-34 into the PU increased the CO 2 /N 2 selectivity by 37% but decreased the CO 2 permeability by about 4%.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, a significant property improvement has been found by using the above metal oxides nanoparticles in the PU matrix. In particular, ZnO nanoparticle enhances the material properties and is being used in many different areas [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%